DIALOGIC INTERACTIVE SPEAKING SKILLS ASSESSMENT IN THE EXPERIENTIAL TEACHING OF TECHNICAL ENGLISH TO TERTIARY SCHOOL STUDENTS - Olesia Liubashenko; Zoia Kornieva (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The article discusses the outcomes of the research on dialogic interactive skills assessment in teaching Technical English to tertiary school students. The authors propose to implement dialogic collaborative interaction as both the medium of instruction and an alternative assessment tool. Theoretically, the study relies on the assumption that Technical English speaking skills acquisition is carried out through different types of communicative interaction and collaborative dialogic interaction in particular. The procedure proposed for speaking skills assessment has been primarily targeted at sustaining oral collaborative interaction along with assessing students' communicative competence. The research represented relies on the experimental teaching English speaking skills to the 1st year Bachelor's students (n=84) at Igor Sikorsky Kyiv Polytechnic Institute. The assessment criteria include conformity of utterances to the topic; speaking tempo; relative grammatical, lexical and phonetic accuracy; cohesion and coherence; compliance with the stylistic and etiquette conventions of English; diversity of grammatical and lexical devices for reaching mutual understanding between the dialogue participants; the interlocutor's speaking initialisation; reaching consensus; and background knowledge deduction. The results of the research confirm that the assessment procedure introduced contributes to boosting oral production if the techniques of supporting collaborative dialogic interaction are applied by the interlocutors. Collaborative dialogue positively affects the development of students' communicative competence and acquisition of such skills as perceiving, understanding and decoding the content of oral texts, identifying the communicative purpose of interlocutor's utterances through analysing verbal and non-verbal means; defining the style and genre of utterances and aligning them with stylistic registers in English.